Sexual Functioning in Experienced Meditators. Issue 5 (4th July 2018) - Dascalu, Iulia; Brotto, Lori A.
ABSTRACT: Given evidence of the benefits of mindfulness for women's sexual difficulties, we investigated the relationship between meditation experience and women's sexual function. Women ( N = 450) answered online survey questions about meditation experience, sexual function and desire, interoceptive awareness, health and mood. Women who meditated scored higher than nonmeditators on measures of sexual function and desire, however there was no significant correlation between frequency/length of meditation experience and either of these domains. Global mental health was a significant predictor of both increased sexual function and desire in women who meditate. These findings suggest that, compared to women with no meditation experience, women who meditate to any extent have, on average, improved sexual function associated with better overall mental health.